ESG Disclosure: Impact on Carbon Footprint Reduction and Increased Market Return of Companies - Susanto, Sheren; Wijaya, Nicholas Lai; Samosir, Ivan Bryan Hotasi; Fitriya, Fitriya (International Journal of Finance Research, 2025)
This study examines the impact of carbon footprint reduction and increased market returns on ESG, aiming to fill the gap in understanding the real effects of ESG reporting, particularly on carbon footprints and market returns in US companies listed on the NASDAQ from 2014 to 2022. The dependent variable of this study is market return, measured from EPS. This study also uses two independent variables to investigate the companies' sustainability (ESG disclosure and GHG scope 1). ESG disclosure exhibits a positive and significant relation towards EPS. On the other hand, GHG scope 1 shows a negative and significant relationship with EPS. This suggests that improved ESG reports and reduced emissions will enhance the company's financial performance, leading to increased EPS and attracting more investors. However, the need for further research to solve the discrepancies and investigate other variables affecting the connection between emissions, financial performance, and ESG disclosure is urgent and of utmost importance.